MCSE Test Success: NT Workstation 4 Exam 70-073 - Lammle, Todd and Donald, Lisa (SYBEX Inc., 1998)
This book is the key to passing Exam 70-073, implementing and supporting Microsoft Windows NT Workstation 4.0$1! =s
Keywords: Computer Networking; Non-Fiction